Essential Oil Yield, Composition, and Antioxidant Activity in Two Umbel Maturity Stages of Wild Carrot (Daucus carota L. ssp. carota) from Montenegro - Jelena Stanojević; Zoran S. Ilić; Ljiljana Stanojević; Lidija Milenković; Renata Kovač; Dragana Lalević; Ljubomir Šunić; Aleksandra Milenković; Dragan Cvetković (Horticulturae, 2023)
The purpose of this study was to determine essential oil yield, composition, and antioxidant activity during two different maturation stages of umbels with seeds(I stage: premature–waxy; and II stage: mature–fully ripening) of wild carrot (Daucus carrota var. carota) from the Montenegrin coast. A higher yield of carrot essential oil (CEO) was determined in mature, fully ripening umbels (1.96 mL/100 g p.m) than in premature umbels at the waxy stage (mL/100 g p.m). Thirty-three components were identified in premature umbels, with β-bisabolene (32.3%), 11-α-(H)-himachal-4-en-1-β-ol (27.9%), elemicin (10.1%), and α-longipipene (7.7%) being the main components. They were followed by α-pinene (3.7%), (E)-asarone (3.4%), (E)-anethole (3.2%), and β-himachalene (2.0%). Thirty-two components were identified in CEO from mature umbels, with β-bisabolene (41.0%), 11-α-(H)-himachal-4-en-1-β-ol(21.1%), elemicin (14.8%), andα-longipipene (5.7%) being the most abundant. These components were followed by (E)-asarone (3.9%), cis-α-bisabolene (2.4%), and β-himachalene (2.0%). The CEO isolated from mature umbelsshowed better antioxidant activity (EC50 value of 31.80 mg/mL) in comparison to the CEO isolated from premature umbels (EC50 value of 49.18 mg/mL) during the incubation time of 60 min. The degree of DPPH radical neutralization increased as the incubation time increased from 20 to 60 min. Therefore, our findings recommend that wild carrot could be harvested in the fully ripening stage when the umbel improves CEO yield and antioxidant activity, without the risk of seed shedding from the umbel and seed losses.